Students' Attitudes towards Research: A Study of Graduate Education Students at a Chinese Normal University - Paul Kakupa; Han Xue (ÜNİVERSİTEPARK Limited, 2019)
This study examined graduate education students' attitudes towards research, and explored the demographic factors associated with those attitudes. Using Papanastasiou's (2014) Revised Attitude towards Research (R-ATR) scale, the study collected data from 100 graduate students of an Education Faculty at a university in northern China. The results showed that the students had moderately positive attitudes towards research. A comparison between Doctoral and Master's degree students revealed that the former had significantly more positive research attitudes, higher self-efficacy, and lower research anxiety than the latter. An increase in the number of research courses taken was significantly associated with lesser research anxiety. Students' generalized self-efficacy was positively associated with their overall attitudes towards research. There was no significant relationship found between age and attitudes towards research. The study concludes by making suggestions about the need to enhance students' positive research attitudes as a means to eliminating research anxiety.